The Effect of Adding Expanded Polystyrene Beads (EPS) on Polymer-Modified Mortar - Mohamed, Z. E.; Al-Hadithi, A. I. (Engineering, Technology & Applied Science Research, 2022)
This study assessed the efficiency of Expanded Polystyrene (EPS) waste as a 10, 20, 30, 40, 50, and 60% substitute for fine aggregate in the manufacturing of lightweight cement composites. A 4% low-cost latex paint emulsion was added to the cement mortar to reinforce it as an alternative to the more expensive polymer admixtures. This improved the bonding between the cement matrix and the EPS particles because SBR films were produced in the cement matrix. The flexural strength of regular EPS concrete may also be significantly increased by SBR treatment. Eight alternative mix designs were created and evaluated for compressive and flexural strength, thermal conductivity, water absorption, and dry density. The polymer-modified mortar was created using a 0.4 water/cement ratio of local cement, polymer, and polystyrene. The results showed that compared to the standard combination at 28 days of aging, the compressive strength increased up to 29.26Mpa, flexural strength increased to 6.83Mpa, dry density increased up to 1930kg/m³, and absorption decreased by 4.95. Thermal conductivity decreased by 0.8291W/m.k.